Perancangan Media Pembelajaran Menggunakan Autoplay pada Mata Pelajaran Animasi 2 Dimensi di SMKN 1 Rao Selatan Kabupaten Pasaman - Harahap, Ahmad Gunawan; Zakir, Supratman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The research was conducted because the author found several problems at SMK N 1 RAO SELATANduring the learning process of 2-dimensional animation subjects. Among them are still limited learning media used in 2-dimensional animation learning, namely